Sikap, Motivasi, dan Minat Berwirausaha Mahasiswa di Surabaya - Ahmad Dzulfikri; Budi Kusworo (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2017)
The growth of entrepreneurial interest cannot be done immediately without any education and training that can drive one's entrepreneurial spirit. This research conducted in NSC Polytechnic Surabaya that aims to analyze attitudes, motivation, and interest of students in running entrepreneurship. This is quantitative research data that obtained by distributing questionnaires to thirty respondents as samples. Sampling was done by simple random sampling technique (random). The data that collected from the survey then processed based on the research procedure and analyzed by multiple linear regression analysis based on SPSS 20. The results of this research indicated that attitudes and motivations had no significant effect on student interest in entrepreneurship.